(untitled) (Indian Journal of Public Health Research & Development, 2026)
Background: Early identification of developmental delay in infancy is crucial for timely intervention, especially in low-resource settings. Pragati Pustak, a culturally adapted parent-reported screening tool, addresses gaps in community-based surveillance for children up to 2 years.​ Objectives: To develop and validate face/content validity and reliability of Pragati Pustak for detecting developmental delays. Methodology: Iterative development via stakeholder focus groups and expert reviews yielded a bilingual, pictorial Yes/No booklet (milestones 3-24 months; warning signs 3-15 months). Face validity used 4-point Likert scales (15 experts, 15 parents). Content validity applied CVI metrics. Reliability assessed KR-20 internal consistency and Cohen’s kappa test-retest (n=6998, 14-day interval).​ Results: Face validity showed ≥80% endorsement. I-CVI ≥0.90; S-CVI/Ave=0.98. KR-20 ranged 0.60-0.95; kappa >0.85 (almost perfect).​ Conclusion: Pragati Pustak offers robust psychometrics, enabling reliable parent-led screening in primary care.